Geochemistry of subsurface water of Swabi district and associated health risk with heavy metal contamination - Ahmad, Laeiq; Waheed, Hamza; Gul, Nida; Sheikh, Lawangin; Khan, Asad; Iqbal, Hasan (Environmental monitoring and assessment, 2022)
Heavy metal (HM) contamination in the drinking water is a serious threat to the consumers and has drawn the global attention. In the current study, twenty six (26) groundwater samples including tube well and domestic bores were collected randomly from fourteen union councils (UCs) of tehsil Swabi. Depth of the tube wells ranged between 100 and 400 feet, while in domestic bore water, it ranged from 22 to 140 feet. Samples were analyzed for different parameters. Concentrations of the heavy metals (HMs) were found in the following increasing orders of Pb > Zn > Cr > Cu > Ni > Cd > Co in domestic well water while in tube well water, the increasing order was Cu > Ni > Co > Zn > Cr > Cd. In the domestic well samples, Cd, Cr, Ni, and Pb were found above the World health organization (WHO), permissible limits. Based on the Water Quality Index (WQI), samples collected from domestic wells were found of poor quality with WQI value of 208, while tube well waters were found of excellent quality, with WQI value of 40. This indicates that domestic well waters are more prone to HM contamination due to low depth. Health risk data showed significantly high risk (HQ > 1) for children upon domestic well water consumption, due to high concentrations of Cr and Pb. No significance relationship was observed between the various parameters which indicate the input of these contaminants from multiple sources.